Sentiment analysis approach towards public opinion on sensitive issues via social media: A way of crisis management control - Zanuddin, Hasmah; Shai, Nursyamira; Othman, Wan Ainun Mior (Primrose Hall Publishing Group, 2020)
Online media is one of the tools of public opinion formation where social media users immediately express their thoughts and perception towards an issue. The process of public opinion formation is described from the start of one's perception, and it depends on the cultural background, past experiences and values. These factors determined one's supporting or opposing an issue. The main objective of this study is to determine the correlations between sensitive issues with negative sentiment builds up among the public. This quantitative content analysis study investigated the influence and relevance of information sources on the distribution of public opinion. There were 4 parameters measured as independent variables, mainly independent sources, conventional sources to the dependent variable, public opinion. The monitoring bodies and regulators utilise the research results in handling sensitive issues in Malaysia. © 2020 Primrose Hall Publishing Group.